2018
DOI: 10.1016/j.explore.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Can Mindfulness Training Improve Medication Adherence? Integrative Review of the Current Evidence and Proposed Conceptual Model

Abstract: Medication adherence is a complex, multi-determined behavior that is often influenced by system- (e.g., cost), drug- (e.g., regimen complexity), and patient-related (e.g., depression) factors. System-level approaches (e.g., making medications more affordable) are critically important but do not address patient-level factors that can undermine adherence. In this paper, we identify patient-level determinants of non-adherence and discuss whether mindfulness-training approaches that target these determinants can h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 95 publications
2
17
0
Order By: Relevance
“…heart conditions, HIV [ 38 ] or schizophrenia [ 19 ]. Following the reports of some authors [ 37 , 38 ] we confirmed the relationship between medication adherence and age.…”
Section: Discussionsupporting
confidence: 86%
“…heart conditions, HIV [ 38 ] or schizophrenia [ 19 ]. Following the reports of some authors [ 37 , 38 ] we confirmed the relationship between medication adherence and age.…”
Section: Discussionsupporting
confidence: 86%
“…For healthcare providers or interventionists designing a mindfulness-based self-care intervention, this underscores the importance of including additional behavior change techniques targeting glucose testing and medication adherence to improve HbA1c. Importantly, there are additional psychological predictors of medication adherence that may be benefited by mindfulness-based intervention, including depressive symptoms, sleep disorders, and life stress (Salmoirago-Blotcher and Carey 2018). Therefore, although we did not find an association between dispositional mindfulness and medication adherence among individuals not receiving mindfulness-based intervention content, fostering state-mindfulness through training may improve adherence behavior indirectly by acting on key psychological predictors of adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has documented a relationship between mindfulness and increased adherence to medications for a variety of health conditions (Salmoirago-Blotcher & Carey, 2017), including HIV treatment adherence (Riley & Kalichman, 2015). In our prior research with HIV-infected youth in Baltimore, Maryland, mindfulness was shown to improve coping and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%